Comparison between nursing students and trainers viewpoints about clinical education environment in Islamic Azad university of Yazd in the year 2006 - Nayereh Salmani; Hengameh Amirian (Kerman University of Medical Sciences, 2006)
Background: Clinical education environment is a place for improving clinical skills of nursing students and preparing them for working in the hospital Studies have shown that students expectation of their clinical education environment is different from what exists in reality That is they are always looking for a better learning environment Therefore finding any factor affecting clinical learning is essential in planning clinical education programs Objectives: To compare nursing students and their instructors viewpoints about clinical education environment Methods: In this descriptive study 119 nursing students and 14 instructors in Islamic University of Yazd were randomly selected Data gathering tool was a twopart questionnaire The first part included demographic features and the second part included items for viewpoint assessment This part contained items about "the relationship between students and their instructors" "the presence of learning opportunities in hospital" "support of students by instructors" and "hospital facilities" Results: Clinical education environment was poor according to 11% moderate according to 77% and good according to 12% of the students while it was evaluated as being moderate by 50% and good by 50% of the instructors and there was significant statistical difference between the two groups in their viewpoints about clinical education environment (p=0001) In addition to the total score in three domains "instructorstudent relationship" "learning opportunities" and support of students by instructor" had better viewpoints comparing to the students (p=0001) Conclusion: The differences between instructors and nursing students viewpoints about the condition of clinical education environment is important and identifying these differences can help recognizing key problems of clinical education environment